Jacques Maritain : an intellectual profile - Dougherty, Jude P., 1930- (Catholic University of America Press, 2003)
"In Jacques Maritain: An Intellectual Profile, Jude P. Dougherty shares his lifetime interest in and study of Maritain with readers. He offers the most complete introduction to Maritain yet to be published, highlighting Maritain's many contributions to philosophy. Throughout, the reader gains a clear sense of Maritain the man, his relationships with other notable figures of his time, and his engagement in many of the debates of the twentieth century."--Jacket